Analisis Penataan Lingkungan Indoor yang Mendukung Kemampuan Pemecahan Masalah (Problem Solving) pada Anak di TK Al-Kamal - Anggi Annisa Pohan; Nita Hayati; Nabila Dwirizki Handayani; Rahmania Hasibuan; Nurlaili Nurlaili (Inovasi Pendidikan dan Anak Usia Dini, 2025)
Early childhood is a golden age, where the formation of behavior begins at that time, because it can influence subsequent growth and development. The implementation of education for all groups and pathways requires good management, especially the classroom environment in early childhood. The environment is very important for children to receive education which must be planned and utilized to be able to support the achievement of children's learning outcomes. An indoor environment is a learning environment that is in a room, such as in a classroom, and is provided by the school for students to study. The problem in this research is about implementing learning by structuring an indoor environment that supports problem solving abilities in early childhood. The type of research used is descriptive qualitative research which aims to describe the analysis of problem solving management in the environment. This research was conducted at Al Kamal Kindergarten which is located on Jalan Tegal Sari Hamlet VI, Percut Sei Tuan District. The research results show that the problem-solving abilities of young children can be improved by arranging the indoor environment with the child's size as a standard, the room is neat, considering the traffic of people when planning a classroom, separating noisy rooms from quiet rooms, classrooms and outdoor areas must be clean, neat and pleasant, how to store learning materials and equipment, placing items that help teacher supervision and arranging the beauty of the classroom.